(untitled) (Global Journal of Human-Social Science, 2024)
During this current period of global business economic and environmental change and with reference to the societal effects of the covid pandemic it is clear that postschool education provision is being subject to a range of competing pressures This paper examines the effects of these changes on current educational provision It examines factors such as possible emergent changes in traditional societal expectations financial barriers to accessing established post-school education and increasing financial pressure on existing education providers to reduce costs and maintain current levels of activity within the existing academic structures Through surveys conducted of employers students and teaching staff possible improvements and adaptations are identified and proposed which may be more effective in meeting the potentially rapidly changing needs of global society in the future